Air drag coefficient of textile-covered elastic cylinders – preliminary aerodynamic studies - Jana Siegmund; Ellen Wendt; Stefan Rothe; Yordan Kyosev; Veit Hildebrandt; Harald Pfifer; Sebastian Schubert; Stefan Schleifenbaum (Communications in Development and Assembling of Textile Products)
This paper presents preliminary experimental results on the influence on the aerodynamic drag of a cylinder from the cylinder type (i.e., rigid or soft) and its textile surface. Both a rigid cylinder and a soft-body cylinder, with a gelatin layer, each with five different textile surfaces were measured in the wind tunnel using force measurement technology. The drag coefficient was determined for several Reynolds numbers. The study shows that the elasticity of a cylinder has a significant influence on the drag force and the airflow type. However, the influence of the soft-body cylinder depends on the respective fabric. With the given measurements, no exact statements can yet be made to quantify the influence. This influence must be studied independently and in conjunction with the textile surface in order to gain understanding of the overall system of airflow, textile and elastic body.